2018
DOI: 10.5005/jp-journals-10024-2260
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Surface Treatments on Biaxial Flexural Strength of Yttria-stabilized Tetragonal Zirconia Polycrystal

Abstract: No negative effect on biaxial flexural strength was observed; indeed, it increases the biaxial strength. Hence, these surface treatments can be done in routine clinical practice to improve the performance of ceramic restoration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Air abrasion with 50 µm and 125 µm AO particles increased the fracture load of 3Y-TZP crowns, but had no influence on their reliability and roughness of the inner occlusal surface, partially accepting the first study hypothesis. This finding is consistent with other studies that reported an increase in the mechanical strength of 3Y-TZP subjected to particle air abrasion 13 - 15 , 20 , 24 .…”
Section: Discussionsupporting
confidence: 93%
“…Air abrasion with 50 µm and 125 µm AO particles increased the fracture load of 3Y-TZP crowns, but had no influence on their reliability and roughness of the inner occlusal surface, partially accepting the first study hypothesis. This finding is consistent with other studies that reported an increase in the mechanical strength of 3Y-TZP subjected to particle air abrasion 13 - 15 , 20 , 24 .…”
Section: Discussionsupporting
confidence: 93%
“…Biaxial flexural strength was measured for the pre-shaded and the liquid-shaded discs using a universal testing machine (39) because it is a widely used machine in research work. (40) The impact of long-term aging must be assessed with the rise in the usage of monolithic entire contour crowns and fixed partial dentures (41) because it might have an impact on the material's optical and mechanical properties, which directly affect the material's suitability for usage in the future (42) .…”
Section: Discussionmentioning
confidence: 99%
“…There is a strong likelihood that embedded abrasive grains will react with fired ceramics, which may result in the formation of cracks in the veneering porcelain [ 21 ]. For example, abrasive blasting may affect the mechanical properties of zirconium oxide [ 26 , 27 ]. Too aggressive action may cause an unfavorable transformation from the tetragonal phase to the undesirable monoclinic (t → m) [ 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, abrasive blasting may affect the mechanical properties of zirconium oxide [ 26 , 27 ]. Too aggressive action may cause an unfavorable transformation from the tetragonal phase to the undesirable monoclinic (t → m) [ 24 , 25 , 26 , 27 , 28 , 29 ]. As the transformation phase increases from the surface of the sample to the entire volume of the sample, microcracks, and residual stresses may develop and decrease the bending force [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%